Remittance and Its Impact on the Stock Market Dynamics: Vector Autoregressive Model - Thapa, Krishna Bahadur (International Journal of Atharva, 2025)
Remittance inflows have become a vital source of income for many developing economies, significantly contributing to national income and influencing economic activities, including stock market dynamics. This study investigates the impact of remittances on the stock market dynamics, focusing on whether remittance inflows contribute to stock market growth and investor behavior. Employing a quantitative approach, the research uses econometric tools like VAR models, co-integration analysis, Granger causality tests, and variance decomposition analysis. Findings reveal that, contrary to earlier studies, remittances have no significant short-term influence on the stock market dynamics. The stock market is primarily driven by its past values, with remittances playing a minimal role in stock price fluctuations. Furthermore, co-integration analysis indicates no long-term relationship between remittances and the stock market, challenging previous assumptions of remittances fostering sustained market growth. The Granger causality test also shows that remittances do not cause stock market movements; rather, the stock index has a marginal influence on remittances. These results suggest that while remittances contribute to liquidity and market stability, their impact on stock market development in Nepal is limited. Policymakers should focus on improving financial infrastructure and investor confidence to better leverage remittances for capital market growth.